Absence of Granzyme B Positive Tumour-Infiltrating Lymphocytes in Primary Melanoma Excisional Biopsies is Strongly Associated with the Presence of Sentinel Lymph Node Metastasis - I. S. van Houdt; B. J. R. Sluijter; P. A. M. van Leeuwen; L. M. Moesbergen; E. Hooijberg; C. J. L. M. Meijer; T. D. de Gruijl; J. J. Oudejans; E. Boven (Cellular Oncology)
Background: Sentinel Lymph Node (SLN) status is strongly related to clinical outcome in melanoma patients. In this study we investigated the possible association between the presence of activated and/or suppressive Tumour Infiltrating Lymphocytes (TILs) and SLN status in clinically stage I/II melanoma patients.